ANALYSIS OF FINE MOTOR SKILLS BY USING A CREATIVE ART MODEL AND COLORING ACTIVITIES IN GROUP B OF AR-ROZAK KINDERGARTEN - Lola Wita Harahap (PG PAUD FIP UNIMED, 2017)
The problem in this study is the low level of fine motor ability of the child in terms of folding, cutting according to the pattern, arranging the toys of building construction, and coloring more neatly and not out of line. This study aims to improve fine motor skills by using creative art models and coloring activities in the group B of Ar-Rozak Kindergarten. This research is a quantitative descriptive study. Subject of this research is student of Group B and object of research is fine motor ability by using creative art model and coloring activity. Methods of data collection used were observation, interview, and documentation. The results showed that fine motor skills through activities in students of Kindergarten of Group B were belonging to category of very good. The data obtained showed that the fine motor skills of the students of Group B of Ar-Rozak Kindergarten were 88.4%. Keywords: Creative Art Model, Coloring, Fine Motor Ability